Aprendentes de educação física escolar na experiência do ateliê biográfico de projeto - Cambiaghi, Rodrigo (Universidade Federal de São Carlos, 2023)
This research had the general objective of investigating the perceptions of Physical Education teachers to identify knowledge in the use of PBW procedures in the overall training process, using educational devices that can adapt the proposal already designed for adults undergoing training procedures, also for students in the fifth year (5th) who are from the public network in the elementary school stage, initial years, in PECC classes. The research methodology was based on epistemological and methodological foundations that recognize the biographical fact, as an essence in relations with knowledge and the dimension of temporality, and the subject who, through his experiences and the specificities of biographical research in education, actions and procedures that organize singular knowledge and its form of socialization, contributed to investigating the Project Biographical Workshop as a training procedure in this field of knowledge. To achieve the methodological objectives of the research, biographical research was adopted, within qualitative characteristics, with collection of verbal materials through a biographical interview of the training narrative type with a CCSPE teacher and analysis of these materials using a reading model and interpretations, everything, described by the field of biographical research in education, based on Delory-Momberger. The results obtained, the actions and procedures, which organize singular knowledge and its form of socialization, validated the PBW as a possible training procedure for this field of knowledge, viable to found a tripod within this relationship, biography and education, between process of biography and training processes. Even pointing to a reduced number of academic publications, aimed at students in the 5th year of the public network in the initial elementary education stage in our country, the PBW was perceived as a procedure capable of balancing knowledge and even overcoming part of the of the training procedures offered today. Much of this was due to the theories investigated, as they opened up spaces for speaking with the world, exposing a form of active listening, with an accessible language, giving clues to the way of being that may be constituting this learning subject and his subjective knowledge, those that produced meaning for the teacher in Physical Education classes.
School physical education learners in the experience of the project biographical workshop
Keywords: Ateliês biográficos de projeto; Educação física; Biografização; Relação com o saber; Subjetividade; Project biographical workshops; Physical education; Biography; Relationship with knowledge; Subjectivity; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO